The Poetry of Twenty-First Century and its Deviation from Arnold’s Traditional Poetic Ideals - Anwar, Maroof; Noor, Fatima; Fatima, Zarish; Bibi, Fatima (Pakistan Journal of Humanities and Social Sciences, 2024)
The study aims to explore present-day poetry from Arnold’s perspective. Poetry, a genre which held the most value in past and was given the prime importance, no more holds the same significance. The study is a qualitative investigation to study the modern-day poetry and its deviation from the classical norms of the poetry. For the purpose, excerpts from the works of four Instapoets were taken and within interpretive paradigm, the analyses were conducted. Arnold, Study of Poetry, was taken as a theoretical framework. The findings of the study shows that the deviation is evident and implausible. The researchers have found that this kind of poetry to be is very plain and simplistic.